2014
DOI: 10.1007/s11886-014-0517-0
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic and Functional Mitral Regurgitation in Heart Failure: Natural History and Treatment

Abstract: Functional mitral regurgitation (FMR) occurs when normal or nearly normal mitral leaflets are prevented from proper coaptation by underlying left ventricular (LV) dysfunction, mitral annular dilation, or both. FMR is associated with an adverse prognosis in nonischemic or ischemic LV dysfunction. Multiple studies have confirmed that even mild FMR portends a worse prognosis, and that the risk of FMR is independent of LV volumes and other clinical risk factors. FMR can be difficult to quantitate echocardiographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 88 publications
0
22
0
3
Order By: Relevance
“…In FMR, tethering of the mitral leaflets is often on the posterior leaflet and particularly on the posteromedial scallop. 24 According to this finding, as the posterior leaflet length increases, tethering of the mitral leaflet diminishes and PM function improves.…”
Section: Discussionmentioning
confidence: 92%
“…In FMR, tethering of the mitral leaflets is often on the posterior leaflet and particularly on the posteromedial scallop. 24 According to this finding, as the posterior leaflet length increases, tethering of the mitral leaflet diminishes and PM function improves.…”
Section: Discussionmentioning
confidence: 92%
“…Some studies provided insight into potential poorer prognosis for patients with functional MR and left ventricular dysfunction and this is especially true for patients with recent acute myocardial infarction and for patients with chronic ischemic and non ischemic cardiomyopathy [14]. It was shown that even with the current GDMT, there was always a tendency to adverse prognosis due to untreated ischemic functional MR.…”
Section: Discussionmentioning
confidence: 99%
“…No two mitral rings are similar and their use is surgeon specific [20][21][22][23]. Broadly, the mitral rings can be classified depending on their rigidity as rigid, semi-rigid, or flexible.…”
Section: Discussionmentioning
confidence: 99%